2023
DOI: 10.1186/s13018-023-04237-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the predictive value of the Geriatric Nutritional Risk Index for osteoporosis in elderly patients with T2DM: a single-center retrospective study

Silu Sun,
Simin Tao,
Xiaoyan Xi
et al.

Abstract: Background Malnutrition is recognized as a risk factor for osteoporosis and T2DM. Previous studies have demonstrated the relationship between nutritional assessment tools and BMD. However, few studies have compared the effects of three nutritional risk assessment tools (GNRI, CONUT, and PNI). This study aimed to investigate the correlation between three nutritional assessment tools and BMD and to compare their validity in predicting osteoporosis in type 2 diabetes mellitus in the elderly. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Moreover, compared with BMI, ALB, and age, GNRI is a more powerful predictor of OP complicating T2DM. It has also been shown that high GNRI (with no nutritional risk) is an independent protective factor for OP in elderly T2DM patients, and it is a stronger predictor of OP in elderly T2DM patients than nutritional scores such as COUNT and PNI 25 . GNRI is used to assess the nutritional status and risk of malnutrition in elderly patients 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with BMI, ALB, and age, GNRI is a more powerful predictor of OP complicating T2DM. It has also been shown that high GNRI (with no nutritional risk) is an independent protective factor for OP in elderly T2DM patients, and it is a stronger predictor of OP in elderly T2DM patients than nutritional scores such as COUNT and PNI 25 . GNRI is used to assess the nutritional status and risk of malnutrition in elderly patients 26 .…”
Section: Discussionmentioning
confidence: 99%